ANALYSIS OF STUDENTS’ EPISTIMOLOGICAL BARRIERS TO SYSTEMS OF TWO VARIABLES LINEAR EQUATIONS (SPLDV) VIEWED FROM ADVERSITY QUOTIENT IN JUNIOR HIGH SCHOOL - Alyani, Fitri; Haidar, Afiful (Prima: Jurnal Pendidikan Matematika, 2024)
This study aims to determine students' epistemological barriers in the material system of two-variable linear equations (SPLDV) in terms of Adversity Quotient (AQ). This research method uses descriptive qualitative. The subjects in this study were 6 students who were selected based on their level, namely Adversity Quotient Climber, Adversity Quotient Camper, and Adversity Quotient Quitter. Researchers used questionnaires, written tests and interviews to determine the extent to which subjects had epistemological barriers and Adversity Quotient (AQ). Then, the data analysis techniques used the Winstep application on questionnaires and written tests, then interviews used data reduction analysis, data collection, and drawing conclusions. The results of this study, namely: a) Students who have high epistemological barriers, have epistemological barriers conceptually, procedurally, and operationally; b) Students who have moderate epistemological barriers have operational epistemological barriers; c) Students who have low epistemological barriers, do not have epistemological barriers conceptually, procedurally, and operationally; d) Students with Adversity Quotient Climbers do not yet have low epistemological barriers, as well as Adversity Quotient Campers and Quitters who do not necessarily have moderate and high epistemological barriers; e) Factors that affect the Adversity Quotient and this epistemological barrier is how students understand the material provided by educators. This research can be a source of information and reference for readers.Keywords: Epistemological Barriers, System of Two Variable Linear Equations, and Adversity Quotient (AQ)